Unveiling the structure of a novel artificial heme‐enzyme with peroxidase‐like activity: A theoretical investigation. Issue 10 (9th August 2018) - Perrella, Fulvio; Raucci, Umberto; Chiariello, Maria Gabriella; Chino, Marco; Maglio, Ornella; Lombardi, Angela; Rega, Nadia
Abstract: Fe(III)‐Mimochrome VI (MC6) is a recently reported artificial heme‐peptide conjugate system with a high peroxidase‐like activity. By design, its structure features a five‐coordinated Fe(III)‐deuteroporphyrin active site, embedded in a compact α‐helix–heme–α‐helix "sandwich" motif. Up to now, no detailed MC6 structural characterization is available. In this work we propose a theoretical investigation based on molecular dynamics (MD) simulations and hybrid quantum mechanics/molecular mechanics (QM/MM) optimizations, aimed to shed light on several Fe(III)‐MC6 structural features and to validate the de novo designed fold. Key structural elements were analyzed to achieve indirect insight relevant to understand Fe(III)‐MC6 catalytic performances in solution. Extensive MD simulations showed a partial stability of the "sandwich" fold in water solution. The smaller peptide chain bonded to the heme revealed a high conformational freedom, which promoted the exposition of the heme distal side to the solvent. Regarding the accessibility of water molecules, even in Fe(III)‐MC6 "closed" structure the heme cavity appeared hydrated, suggesting an easy accessibility by exogenous ligands. Fe(III)‐MC6 structure in both high and low spin states was then further characterized through hybrid QM/MM optimizations. In particular, an accurate description of the active site structure was obtained, allowing a direct comparison of Fe(III)‐MC6 coordination environment with that observed in the Horseradish Peroxidase crystal structures. Our results suggest a structural similarity between Fe(III)‐MC6 and the natural enzyme. This study supports the interpretation of data from experimental Fe(III)‐MC6 structural and functional characterization and the rational design of new artificial mimics with improved catalytic performances. Abstract :